Morphology of the 13CO(3–2) millimetre emission across the gas disc surrounding the triple protostar GG Tau A using ALMA observations. (March 2018) - Phuong, Nguyen Thi; Diep, Pham Ngoc; Dutrey, Anne; Chapillon, Edwige; Darriulat, Pierre; Guilloteau, Stéphane; Hoai, Do Thi; Nhung, Pham Tuyet; Tang, Ya-Wen; Thao, Nguyen Thi; Tuan-Anh, Pham
Abstract: Observations by the Atacama Large Millimetre/sub-millimetre Array of the dust continuum and 13 CO(3–2) millimetre emissions of the triple stellar system GG Tau A are analysed, giving evidence for a rotating gas disc and a concentric and coplanar dust ring. The present work complements an earlier analysis (Tang et al.) by exploring detailed properties of the gas disc. A 95% confidence level upper limit of 0.24″ (34 au) is placed on the disc scale height at a distance of 1″ (140 au) from the central stars. Evidence for Keplerian rotation of the gas disc is presented, with the rotation velocity reaching ∼3.1 km s −1 at 1″ from the central stars, and a 99% confidence level upper limit of 9% is placed on relative contribution from a possible in-fall velocity. Variations of the intensity across the disc area are studied in detail and confirm the presence of a hot spot in the south-eastern quadrant. However several other significant intensity variations, in particular a depression in the northern direction, are also revealed. Variations of the intensity are found to be positively correlated to variations of the line width. Possible contributions to the measured line width are reviewed, suggesting an increase of the disc temperature and opacity with decreasing distance from the stars.